2006
DOI: 10.1128/jb.01349-06
|View full text |Cite
|
Sign up to set email alerts
|

Heme Biosynthesis in Methanosarcina barkeri via a Pathway Involving Two Methylation Reactions

Abstract: The methanogenic archaeon Methanosarcina barkeri synthesizes protoheme via precorrin-2, which is formed from uroporphyrinogen III in two consecutive methylation reactions utilizing S-adenosyl-L-methionine. The existence of this pathway, previously exclusively found in the sulfate-reducing ␦-proteobacterium Desulfovibrio vulgaris, was demonstrated for M. barkeri via the incorporation of two methyl groups from methionine into protoheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…However, increasing amounts of genome sequencing data started to reveal some interesting insights into heme biosynthesis. In particular, most archaeal genomes were found to be missing orthologs of hemE, hemF or hemN, hemG or hemY, and hemH even though these genomes also encoded a number of hemoproteins, highlighting the fact that they must be able to make heme through some alternative process (176). A similar observation was also made for the genomes of sulfate-reducing bacteria, including that of D. vulgaris (177).…”
Section: Prokaryotic Heme Biosynthesismentioning
confidence: 54%
See 2 more Smart Citations
“…However, increasing amounts of genome sequencing data started to reveal some interesting insights into heme biosynthesis. In particular, most archaeal genomes were found to be missing orthologs of hemE, hemF or hemN, hemG or hemY, and hemH even though these genomes also encoded a number of hemoproteins, highlighting the fact that they must be able to make heme through some alternative process (176). A similar observation was also made for the genomes of sulfate-reducing bacteria, including that of D. vulgaris (177).…”
Section: Prokaryotic Heme Biosynthesismentioning
confidence: 54%
“…Moreover, this result demonstrated that the alternative pathway was likely to be much more widespread than previously thought, representing the major pathway for heme synthesis within the archaeal kingdom of life (176). This prompted a more detailed bioinformatic approach in order to help identify the proteins and enzymes associated with the transformation of uroporphyrinogen III into heme within the Archaea.…”
Section: Prokaryotic Heme Biosynthesismentioning
confidence: 92%
See 1 more Smart Citation
“…The modern haem pathway, as shown in figure 1, might have evolved from a prototype resembling the siro-haem synthesis, which uses only three enzymatic steps from Urogen III via the intermediate precorrin-2 [5]. This is supported by the fact that archaea synthesize haem via the precorrin-2 pathway [27]. Furthermore, precorrin-haem could have evolved from an even earlier corrin-based tetrapyrrole molecule (figure 3a).…”
Section: The Origin and Evolution Of Three Tetrapyrrole Branchesmentioning
confidence: 99%
“…euka- ryotischen Syntheseweg unterscheidet. Schon seit Mitte der 1990er-Jahre weiß man, dass dieser "alternative" Hämbiosyntheseweg über das Intermediat Precorrin-2 verläuft [2,7]. Bioinformatische Analysen der Verbreitung der bekannten, für die "herkömmliche" Häm-biosynthese in Bakterien benötigten hemGene zeigten, dass die frühen Hämbiosyn-thesegene hemA, hemL, hemB, hemC und hemD, deren Proteinprodukte für die Bildung von Uroporphyrinogen III verantwortlich sind, in Archaea vorhanden sind [8,9].…”
Section: Verwandtschaft Der Häm-d 1 -Biosynthese Mit Der Hämbiosyntheunclassified